The Impact of Social Factor in The Urbanization of The Population of The City of Hama (Journal of Hama University, 2020)
This study aimed at presenting and analyzing the social factor in the elaboration of the elements of the modern urban character of the city of Hama and its social construction, as this factor is a key element in the urban system, which is the crucible where the various factors interact with each other, eventually forming the features of the urban character of any city.The study adopted the descriptive analytical method to achieve its objectives, and showed that the social factor played an important role in the spatial organization of the population and urbanization within the city before the emergence of urban planning activities. This factor has a direct impact on population distribution, urbanization and land use patterns. In addition, it has given the city the importance of this factor in the formation of the urban character of the city, to take advantage of urban planning of the existing social data, and then works to employ them positively and effectively in its various activities in a way that can achieve its goals and objectives.